Talent Management : Leading for the future - Kaushik, Shriam; Legnerová, Kateřina, 1965-; Černá, Daniela; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
The main purpose of the master's thesis is to study the factors and experiences that may influence Gen Z to stay in an organization for longer periods of time with a focus on Work-life balance, in the post-Covid era that comes with changes in the environment, society and even priorities of the new generation. The research focused on work life balance due to the ongoing TikTok trends such as #quittok and also explored economic trends such as “the great resignation”. For this study 14 Gen Z employees who have recently started or are already working in the corporate sector, and study at the Prague university of economics and business were interviewed. The qualitative data was collected and analysed on to the 4 main thematic sections, namely: ‘schedule and spatial flexibility’, ‘non-monetary benefits’, ‘external activities’, ’employer brand’. Analysis of each of these four sections helped in completing the thesis, providing answers to the research questions, and coming to a conclusion.
Vedoucí práce: Kateřina Legnerová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses